Conservation Methods Applied at Registan Square (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Registan Square in Samarkand, Uzbekistan, is one of the most emblematic monuments of Islamic and Timurid architecture. Over the past century, it has undergone multiple conservation campaigns reflecting shifts in political context, technological capabilities, and evolving philosophies of heritage preservation. This paper explores the major conservation methods employed from the Russian Imperial period through the Soviet era to contemporary efforts in post-independence Uzbekistan. It analyzes the application of structural reinforcement, material restoration, digital technologies, and international collaboration, evaluating their adherence to global conservation ethics. By tracing these interventions in chronological and thematic order, the study highlights the balance between material preservation and authenticity, offering insights into sustainable heritage management in a historically and seismically vulnerable context.